Development of the Pentuple Bottom Line Model in Moderating the Influence of Financial Literacy and Financial Inclusion on the Sustainability of Msmes in West Java - Eris Juliansyah; Sukrisno Agoes; Nurmala Ahmar (Greenation Research & Yayasan Global Resarch National, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy, including in West Java Province, especially MSMEs assisted by the West Java Provincial Disduk with more than 7 thousand units in 2022-2023. Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy, including in West Java Province, especially MSMEs assisted by the West Java Provincial Disduk with more than 7 thousand units in 2022-2023. However, the sustainability of MSMEs faces significant challenges, such as low financial literacy, limited access to formal financing, and minimal adoption of digital technologies. This study aims to analyze the influence of financial literacy and financial inclusion on MSME sustainability and examine the moderating role of the Pentuple Bottom Line (PBL) concept. PBL expands the Triple Bottom Line framework by incorporating spirituality and technology as additional dimensions. The research adopts a quantitative approach using primary data collected from 380 MSME respondents in West Java. The findings indicate that financial literacy and financial inclusion positively affect MSME sustainability, and PBL significantly moderates these relationships. This study enriches the discourse on MSME sustainability through a multidimensional approach and offers policy recommendations grounded in spiritual values and technological advancement